SISTEM PENGUKURAN KINERJA DENGAN METODE PERFORMANCE PRISM (Studi Kasus di RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG) - Prastawa, Heru; Pujotomo, Darminto; Arvianto, Ary; Khoirunnisa, Fithria (Diponegoro University, 2011)
Sultan Agung Islamic Hospital Semarang is a healthcare institution owned by Yayasan Badan Wakaf SultanAgung. To survive against the competitors, the hospital must have a good performance. Thus, a properperformance measurement system is required to assist the company in informing the hospital, so they know howfar has their effort worked in achieving the company’s vision and mission, including to analyze how far has thecompany developed. The researcher intends to design a performance measurement system using theperformance prism method at Sultan Agung Islamic Hospital Semarang. Designing a performance measurementsystem by implementing the performance prism method is sequenced by several phases. Firstly, identify thesatisfaction and stakeholder’s contribution, strategy identification phase, process, and capability, KeyPerformance Indicator (KPI) identification phase, weighing KPI by Analytical Hierarchy Process (AHP) phase,achieving performance targets by an Objective Matrix (OMAX) phase, and the calculation phase of performancevalue in numbers. After we calculate the weighed KPI and performance value, a simulation is conducted to knowthe criteria and KPI elements that is prioritized a suggestion, improvement recommendation that could beapplied to enhance the performance of Sultan Agung Islamic Hospital Semarang